Challenges to implementing Gavi's health system strengthening support in Chad and Cameroon: results from a mixed-methods evaluation - Emily Dansereau; Yodé Miangotar; Ellen Squires; Honoré Mimche; UND group; IFORD group; Charbel El Bcheraoui (BMC, 2017)
Abstract Background Since 2005, Gavi has provided health system strengthening (HSS) grants to address bottlenecks affecting immunization services. This study is the first to evaluate the Gavi HSS implementation process in either Cameroon or Chad, two countries with significant health system challenges and poor achievement on the child and maternal health Millennium Development Goals. Methods We triangulated quantitative and qualitative data including financial records, document review, field visit questionnaires, and key informant interviews (KII) with representatives from the Ministries of Health, Gavi, and other partners. We conducted a Root Cause Analysis of key implementation challenges, guided by the Consolidated Framework for Implementation Research. Results We conducted 124 field visits and 43 KIIs in Cameroon, and 57 field visits and 39 KIIs in Chad. Cameroon's and Chad's HSS programs were characterized by delayed disbursements, significant deviations from approved expenditures, and reprogramming of funds. Nearly a year after the programs were intended to be complete, many district and facility-level activities were only partially implemented and significant funds remained unabsorbed. Root causes of these challenges included unpredictable Gavi processes and disbursements, poor communication between the countries and Gavi, insufficient country planning without adequate technical assistance, lack of country staff and leadership, and weak country systems to manage finances and promote institutional memory. Conclusions Though Chad and Cameroon both critically needed support to strengthen their weak health systems, serious challenges drastically limited implementation of their Gavi HSS programs. Implementation of future HSS programs in these and similar settings can be improved by transparent and reliable procedures and communication from Gavi, proposals that account for countries' programmatic capacity and the potential for delayed disbursements, implementation practices that foster learning and adaptation, and an early emphasis on developing managerial and other human resources.